1990
DOI: 10.1056/nejm199011013231802
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis and Colorectal Cancer

Abstract: Close surveillance and perhaps even prophylactic proctocolectomy should be recommended for patients given a diagnosis of pancolitis, especially those who are less than 15 years of age at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
781
6
60

Year Published

1995
1995
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,640 publications
(858 citation statements)
references
References 25 publications
11
781
6
60
Order By: Relevance
“…Patients with longstanding IBD are at increased risk for developing colon cancer (64). Neoplasia develops in the context of increased epithelial cell turnover and regeneration induced by the chronic inflammatory state (65).…”
Section: Mpges-1 and Inflammatory Bowel Diseasementioning
confidence: 99%
“…Patients with longstanding IBD are at increased risk for developing colon cancer (64). Neoplasia develops in the context of increased epithelial cell turnover and regeneration induced by the chronic inflammatory state (65).…”
Section: Mpges-1 and Inflammatory Bowel Diseasementioning
confidence: 99%
“…Sheng et al (10) have suggested that there is a connection between inflammation and the development of cancer, which is also supported by results showing that ulcerative colitis is associated with an increased incidence of neoplastic transformation (11) and the observation that colon cancer is underrepresented in populations treated with nonsteroidal anti-inflammatory drugs (12). Furthermore, in previous experiments using nontransformed intestinal epithelial cells (13), we found that prolonged exposure to LTD 4 resulted in up-regulation of several proteins associated with colon carcinogenesis, among others cyclooxygenase-2, ␤-catenin, and the cell survival protein Bcl-2 (13,14).…”
supporting
confidence: 53%
“…Generally, the cumulative incidence of CRC in patients with UC has an increasing trend. For instance, at 20, 30 and 35 years after diagnosis of UC, the percentage of UC-diagnosed patients afflicted with CRC was 5-10%, ISSN: 2198-4093 www.bmrat.org 12-20%, and 30%, respectively (Ekbom et al, 1990;Gyde et al, 1988). There are other factors that may be associated with the risk of developing CRC in patients with IBD.…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%